Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.xcrm.2020.100160
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Immune Checkpoints by Chemotherapy in Human Colorectal Liver Metastases

Abstract: Summary Metastatic colorectal cancer (CRC) is a major cause of cancer-related death, and incidence is rising in younger populations (younger than 50 years). Current chemotherapies can achieve response rates above 50%, but immunotherapies have limited value for patients with microsatellite-stable (MSS) cancers. The present study investigates the impact of chemotherapy on the tumor immune microenvironment. We treat human liver metastases slices with 5-fluorouracil (5-FU) plus either irinotecan or oxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 44 publications
(71 reference statements)
0
23
0
Order By: Relevance
“…Previous study showed that the expression of PD-L1 was increased in liver metastases compared to primary CRC, indicating different intrinsic microenvironment between primary and metastatic CRC [ 110 ], which may help CRC liver metastases escape from immune surveillance. In addition, it was reported that chemotherapy can modulate PD-L1 and TIM-3 expression in CRC liver metastases, suggesting the potential strategy of combined chemo-immunotherapies [ 111 ]. Preclinical study showed that dual CTLA4 and PD-1 blockade could significantly suppress colon cancer growth and liver metastasis by enhancing T cell responses and M1 macrophage polarization [ 112 ].…”
Section: Liver Immune Microenvironment For Crc Liver Metastasismentioning
confidence: 99%
“…Previous study showed that the expression of PD-L1 was increased in liver metastases compared to primary CRC, indicating different intrinsic microenvironment between primary and metastatic CRC [ 110 ], which may help CRC liver metastases escape from immune surveillance. In addition, it was reported that chemotherapy can modulate PD-L1 and TIM-3 expression in CRC liver metastases, suggesting the potential strategy of combined chemo-immunotherapies [ 111 ]. Preclinical study showed that dual CTLA4 and PD-1 blockade could significantly suppress colon cancer growth and liver metastasis by enhancing T cell responses and M1 macrophage polarization [ 112 ].…”
Section: Liver Immune Microenvironment For Crc Liver Metastasismentioning
confidence: 99%
“…The tumor slice culture method can be used to study tumor response to chemotherapies, immunotherapies, or combined chemo-immunotherapies. In previously published work ( Jabbari et al., 2020 ) the response of human colorectal liver metastases (CRLM) treated with chemotherapy and immunotherapy combinations was evaluated utilizing tissue slice cultures. Here we show an example of a case of CRLM treated with two different chemotherapy combinations with endpoints for tumor response including viability (based on percent change in MTS absorbance), histology including immunohistochemistry, and single-cell RNA sequencing.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“… (B) Another set of treated slices were used to perform single-cell RNA sequencing. Figure reprinted with permission from Jabbari et al, 2020 . Note how slices are dispersed over the treatment and endpoint assay.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 2 more Smart Citations